2007
DOI: 10.1586/14787210.5.4.591
|View full text |Cite
|
Sign up to set email alerts
|

Systemic rotavirus infection

Abstract: A new paradigm of rotavirus disease is emerging and rotavirus infection is no longer considered to be localized and confined to the GI tract. New evidence indicates that rotavirus infection is systemic. Viral antigen and infectious virus frequently enter the circulation in both children and animal model systems. Clinical case reports of systemic sequelae to rotavirus infection in children continue to accumulate, suggesting involvement in systemic disease syndromes. The use of animal models is providing biologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0
5

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(72 citation statements)
references
References 103 publications
2
65
0
5
Order By: Relevance
“…Rotavirus infection is usually localized to the intestine; however, recent studies reported antigenemia or viremia in children with rotavirus diarrhea (11,12,17,18,90). Rarely, involvement of extraintestinal sites, including the respiratory tract, liver, kidney, lymph nodes, and central nervous system, has been reported (54,55,64,70).…”
Section: Introductionmentioning
confidence: 99%
“…Rotavirus infection is usually localized to the intestine; however, recent studies reported antigenemia or viremia in children with rotavirus diarrhea (11,12,17,18,90). Rarely, involvement of extraintestinal sites, including the respiratory tract, liver, kidney, lymph nodes, and central nervous system, has been reported (54,55,64,70).…”
Section: Introductionmentioning
confidence: 99%
“…[94] Rotavirus infections rarely cause other complications and for a well managed child the prognosis is excellent. [95] …”
Section: Markers Of Protectionmentioning
confidence: 99%
“…It has 102 been reported that group A rotavirus was detected in some tissues of domestic and 103 experimental animals (Ramig, 2007). To assess the infection of the bat by LUS12-14, we 104 extracted RNA from the spleen, lung, kidney and liver tissues of the bat in which 105 LUS12-14 was detected in the intestinal contents.…”
Section: (Rhinolophus Simulator) 83mentioning
confidence: 99%